Development of an athlete diet index for rapid dietary assessment of athletes - Capling, L.; Gifford, J. A.; Beck, K. L.; Flood, V. M.; Slater, G. J.; Denyer, G. S.; O`Connor, H. T. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Food-based diet indices provide a practical, rapid, and inexpensive way of evaluating dietary intake. Rather than nutrients, diet indices assess the intake of whole foods and dietary patterns, and compare these with nutrition guidelines. An athlete-specific diet index would offer an efficient and practical way to assess the quality of athletes` diets, guide nutrition interventions, and focus sport nutrition support. This study describes the development and validation of an Athlete Diet Index (ADI). Item development was informed by a review of existing diet indices, relevant literature, and in-depth focus groups with 20 sports nutritionists (median of 11 years` professional experience) from four elite athlete sporting institutes. Focus group data were analyzed (NVivo 11 Pro; QSR International Pty. Ltd., 2017, Melbourne, Australia), and key themes were identified to guide the development of athlete-relevant items. A modified Delphi survey in a subgroup of sports nutritionists (n = 9) supported item content validation. Pilot testing with athletes (n = 15) subsequently informed face validity. The final ADI (n = 68 items) was categorized into three sections. Section A (n = 45 items) evaluated usual intake, special diets or intolerances, dietary habits, and culinary skills. Section B (n = 15 items) assessed training load, nutrition supporting training, and sports supplement use. Section C (n = 8 items) captured the demographic details, sporting type, and caliber. All of the athletes reported the ADI as easy (40%) or very easy (60% of participants) to use and rated the tool as relevant (37%) or very relevant (63% of participants) to athletes. Further evaluation of the ADI, including the development of a scoring matrix and validation compared with established dietary methodology, is warranted.